More lovely knitted lace : contemporary patterns in geometric shapes - Nico, Brooke (Lark, 2016)
"Brooke Nico, author of Lovely Knitted Lace and a nationally known lace teacher and designer, presents 16 new projects that offer a fresh and original take on lace knitting. Think sweaters, capelets, tunics and cowls, knit in yarns both thick and thin--contemporary designs that give knitters a wealth of new possibilities. Organized by overall shape--circle, square, triangle, and rectangle--these lovely garments will change the way you look at lace knitting. Step-by-step illustrations clearly explain any advanced techniques, while every pattern regardless of difficulty contains both written and charted instructions. Carrie Hoge, well known for her images for the Quince & Co yarn brand, contributes gorgeous and inspiring photos."-- Amazon.com.